IMPROVING STUDENT PRONUNCIATION SKILL THROUGH READING ALOUD AT 8TH GRADE STUDENTS OF SMP WIDURI JAYA JAKARTA - BIBYANA BIBYANA; SYAMSI EDI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
The aim of the research is to describe the impact of reading aloud against the English pronunciation skill of 8th grade students in SMP Widuri Jaya for academic year 2022/2023. The research used pre-experimental method consists of pre-test, treatment, and post-test. There are 17 students involved in pronunciation assessment of 9 fricative consonants. The score of Pre-Test and Post-Test classified into several criteria and analyzed to get the statistical comparison of prior treatment against after treatment. In the Pre-Test, students’ pronunciation was very poor classified. After treatment, the mean score of the students increases for about 90% compared to the pre-test score. According to the Paired Sample t-test that used to validate the hypotheses of the research, it can be concluded that there is significant impact between reading technique against the student’s improvement of English pronunciation. By consistently practicing reading aloud, the students’ English pronunciation can be improved. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh membaca nyaring terhadap pelafalan Bahasa Inggris pada siswa kelas delapan di SMP Widuri Jaya tahun ajaran 2022/2023. Penelitian ini bersifat eksperimental yang terdiri dari 3 tahap yaitu Pre-Test, tindakan kelas, dan Post-Test. Sebanyak 17 siswa dilibatkan untuk penilaian pelafalan 9 konsonan frikatif. Hasil pre-test dan post-test diklasifikasikan ke dalam beberapa kriteria dan dianalisa untuk memperoleh perbanding statistikal sebelum dan sesudah tindakan kelas. Saat Pre-Test, nilai pelafalan Bahasa Inggris para siswa dikategorikan sangat rendah. Setelah tindakan kelas, nilai rata-rata siswa telah meningkat sebanyak 90% dibandingkan hasil penilaian saat Pre-Test. Berdasarkan uji hipotesis penelitian dengan Teknik Paired Sample T-Test, dapat disimpulkan terdapat pengaruh yang signifikan antara Teknik membaca para siswa dengan peningkatan kemampuan mereka dalam pelafalan Bahasa Inggris. Dengan mempraktekkan membaca nyaring secara konsisten, kemampuan pelafalan Bahasa Inggris para siswa dapat meningkat.